Studies on Affecting Factors of Wheel Slip and Odometry Error on the Performance of Wheeled Mobile Robots – A Review - Vidhya Prakash (Institute of Advanced Engineering and Science, 2016)
The wheeled mobile robots (WMR) find use for doing a variety of tasks in different types of workspaces. These workspaces are form of ideal natural flat, smooth terrain, unpredictable and irregular nature of these work spaces demanding a design challenges. Typically there work spaces may have pits, undulatory is not flat terrain, obstacles into tasks of the robot. There would result in wheel slippage orodometry error. This tasks a toll in the form of deviation from intended trajectory, navigation, travel time &budgeted energy consumption. These engineering issues can be addressed by proper design of wheel rotation, vibration amplitude of the robot body, travel time modulation differently up to the terrain condition (wet, dry, soft, hard)&wind effect. The wheel slip & odometry error is estimate of computational by design, pay load distribution, speed, wheel diameter, wheel width are the ply able design parameter in the designness scope. The effect of proper selection of the values of there parameters is studied in this review. The paper reviews are analyzing the basic& direct effect of parameters are how to associate with wheel slippage and odometry error and also which is the most affecting factor on the wheeled mobile robots.